PENERAPAN PERSAMAAN PADA POKOKNYA BERUPA UNSUR NAMA MEREK DALAM GUGATAN PEMBATALAN MEREK: PENERAPAN PERSAMAAN PADA POKOKNYA BERUPA UNSUR NAMA MEREK DALAM GUGATAN PEMBATALAN MEREK - Jacksumet, Julinus; Sahat Marulitua Sidabukke (Faculty of Law-Universitas Bandar Lampung, 2024)
Trademark registration in Indonesia requires strong distinguishing power to differentiate a brand, which identifies the origin and characteristics of a product or service. Under Article 21, paragraph (1) of Law Number 20 of 2016, trademarks lacking this power will be denied registration. However, the inconsistency in handling trademark disputes in Indonesia often leads to a lack of legal certainty. Some judges focus only on auditory similarities, ignoring visual differences, while others consider all elements, including visual appearance and product type. This study examines the application of the principle of equality in trademark cancellation lawsuits prioritizing name elements. Utilizing normative legal methods through literature studies, legal references, and interviews, the findings reveal that a brand's distinguishing power is significantly influenced by the pronunciation of its name, which contributes unique meanings and identities, setting it apart from other registered brands.